2008
DOI: 10.1093/occmed/kqn092
|View full text |Cite
|
Sign up to set email alerts
|

Employment in a cohort of breast cancer patients

Abstract: Breast cancer survivors in this study encountered some problems in returning to work, mainly linked to the sequelae of their disease and its treatment rather than to discrimination by employers or colleagues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 8 publications
6
34
3
3
Order By: Relevance
“…The adverse effect of cancer progress and poor physical functioning on RTW has been shown in several previous studies (7,23,27). Corresponding to previous research, we found reemployment significantly associated with younger age and a professional status as an employee (24,27,45). Our regression analyses findings emphasize the importance of volitional factors for RTW.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The adverse effect of cancer progress and poor physical functioning on RTW has been shown in several previous studies (7,23,27). Corresponding to previous research, we found reemployment significantly associated with younger age and a professional status as an employee (24,27,45). Our regression analyses findings emphasize the importance of volitional factors for RTW.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the literature, the perceived employer accommodation indicated a fairly positive attitude towards employment, work-related support, and necessary job changes (14,27,49) and emerged as a significant predictor for RTW.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is however quite unsettling and can easily be interpreted as a form of discrimination. This has previously been identified by [16], although conversely, [38], report job discrimination was not experienced by their participants.…”
Section: Discussionsupporting
confidence: 62%
“…Dass einige Patientinnen dabei jedoch nicht den Umfang vor der Diagnosestellung erreichen, verdeutlicht eine Längsschnittstudie an Brustkrebspatientinnen [52]. Im Vergleich zu Frauen und Männern ohne Krebserkrankung ergeben drei Studien bei Patientinnen keine [40,48] Eine Studie an Brustkrebspatientinnen berichtet, dass die Mehrheit der Patientinnen ihre Diagnose Kollegen und Arbeitgebern mitteilt [59], während in einer früheren Studie nur 41% der Brustkrebspatientinnen ihren Vorgesetzten informiert haben [29]. Keine der quantitativen Studien untersucht systematisch die Rücksichtnahme des Arbeitgebers auf erkrankungs-und behandlungsbedingte Bedürfnisse von Patientinnen und Patienten.…”
Section: Arbeitssituationunclassified